2022
DOI: 10.5089/9798400224430.001
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Communication and Financial Markets in India

Abstract: IMF Working Papers describe research in progress by the author(s) and are published to elicit comments and to encourage debate. The views expressed in IMF Working Papers are those of the author(s) and do not necessarily represent the views of the IMF, its Executive Board, or IMF management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Monetary policy should focus on ensuring price stability, while communication can be enhanced to reduce uncertainty and help guiding market expectations. Ahmed, Binici, and Turunen (2022) found that Reserve Bank of India's forward guidance played an important role in moderating uncertainty and supporting asset prices during the pandemic.…”
Section: Monetary and Fiscal Policy Based On Clear Communication And ...mentioning
confidence: 99%
“…Monetary policy should focus on ensuring price stability, while communication can be enhanced to reduce uncertainty and help guiding market expectations. Ahmed, Binici, and Turunen (2022) found that Reserve Bank of India's forward guidance played an important role in moderating uncertainty and supporting asset prices during the pandemic.…”
Section: Monetary and Fiscal Policy Based On Clear Communication And ...mentioning
confidence: 99%